Tumor-specific NIR-activatable nanoreactor for self-enhanced multimodal imaging and cancer phototherapy - Feng, Lili (2023)
Responsive nanosystems for tumor treatment with high specificity and sensitivity have aroused great attention. Herein, we develop a tumor microenvironment responsive and near-infrared (NIR)-activatable theranostic nanoreactor for imaging-guided anticancer therapy. The nanoreactor (SnO2–x@AGP) is comprised of poly(vinylpyrrolidine) encapsulated hollow mesoporous black SnO2–x nanoparticles coloaded with glucose oxidase (GOx) and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). The constructed nanoreactor can be specifically activated through endogenous H2O2 by an NIR-mediated “bursting-like” process to enhance its imaging and therapeutic functions. Black SnO2–x with abundant oxygen vacancies expedites effective separation of electron–hole pairs from energy-band structure and endows them with strong hyperthermia effect upon NIR laser irradiation. The generating toxic H2O2 with the assistance of GOx provides SnO2–x@AGP with the capacity of oxidative stress therapy. Ascended H2O2 can activate ABTS into ABTS•+. ABTS•+ not only possesses significant NIR absorption properties, but also disrupts intracellular glutathione to generate excessive reactive oxygen species for improved phototherapy, leading to more effective treatment together with oxidative stress therapy. Thus, SnO2–x@AGP with NIR-mediated and H2O2-activated performance presents tumor inhibition efficacy with minimized damage to normal tissues. These outstanding characteristics of SnO2–x@AGP bring an insight into the development of activatable nanoreactors for smart, precise, and non-invasive cancer theranostics.